Analysis on the pattern and driving factors of industrial wastewater discharge in the Wuhan Metropolitan area. Issue 6 (17th May 2022) - Liu, Shuai; Liu, Xiaoqiong; Ma, Bowen; Ding, Zewei; Chen, Kunlun
Abstract: As China's ecological civilization gains momentum and the ecological development of the 'Yangtze River Economic Belt' strategy pushes forward, the research on water environment protection and management in Wuhan Metropolitan Area (the central urban agglomeration) is of great significance. According to the data of the industrial wastewater discharge in the nine cities of the Wuhan Metropolitan Area from 2005 to 2015, the study will construct a decomposition model to analyze the pattern of the discharge with reference to the Kaya identity and the LMDI decomposition model. By doing so, the pattern and driving factors of industrial wastewater discharge can be cleared. The following conclusions on the industrial wastewater discharge of the Wuhan Metropolitan Area can be achieved. Firstly, industrial wastewater discharge in the Wuhan Metropolitan Area shows a decreasing trend year by year (684 million tons to 433 million tons) from 2005 to 2010, but rises sharply (504 million tons to 652 million tons) from 2010 to 2011, reaching a peak in 2011. After that, it witnesses a quick and stable drop. Secondly, the absolute differences in industrial wastewater discharge among cities are continuously narrowed, in which Wuhan (the highest value is 260 million tons, the lowest value is 155 million tons) and Ezhou (the highest value is 181 million tons, the lowest value is 0.25 million tons) show the most striking abnormal statistics. Thirdly, the discharge follows the trend of expansion from Wuhan as a center to its neighboring cities from 2005 to 2015. For spatial pattern, it presents a picture of decreasing from the center to the surrounding. Lastly, for all driving factors affecting the discharge, the contribution of economic growth is always positive, which can increase the discharge greatly (the average annual contribution reaches 0.64 billion m 3 ). The population size has little effect. The industrial structure has an uncertain influence on it since it is decided by government policies. The influence of technological improvement is negative, which can control the discharge a lot. In the last part of this essay, the research will explore the ways to promote the saving and discharge reduction of industrial wastewater for future potential metropolitan areas, thus providing a reference for macro water environment protection and governance in the Yangtze River Basin and other regional urban areas. HIGHLIGHTS: The statistical data of industrial wastewater discharge (2005–2015) are analyzed. The decomposition model of industrial wastewater discharge is constructed. Decomposing the factors into technological improvement, industrial structure, economic growth, and the population size. The temporal and spatial characteristics and driving factors are defined. Guiding the protection and control of macro viewing water environment.